2005
DOI: 10.1017/s1041610205002437
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of depression in late life versus mid-life: implications for the treatment of older adults

Abstract: Depression in late life is extremely common. Of those aged 65 years or older, 2–5% have syndromal depression, but up to 20% of elderly people have depressive symptoms (Horwath et al., 2002). Both syndromal and subsyndromal depression carry a high risk of long-term complications and both are associated with elevated risks of morbidity and mortality (Penninx et al., 1999). Despite repeated alerts, depression is consistently under-recognized in acute medical settings, in nursing homes and in primary care (Volkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…By examining the natural history of depressed older patients, Roth found that many of them recovered fully, even when they were quite old. Subsequent research has explored the differences between younger and older adults in the incidence, prevalence, natural history, and treatment outcomes of depression (Schneider, Reynolds, Lebowitz, & Friedhoff, 1994; Subramaniam & Mitchell, 2005), but among older adults the association of advancing age with depression is less clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By examining the natural history of depressed older patients, Roth found that many of them recovered fully, even when they were quite old. Subsequent research has explored the differences between younger and older adults in the incidence, prevalence, natural history, and treatment outcomes of depression (Schneider, Reynolds, Lebowitz, & Friedhoff, 1994; Subramaniam & Mitchell, 2005), but among older adults the association of advancing age with depression is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Sickness and poor health have been posited as a cause of depression in aging adults; as a recent textbook of geriatric mental health notes, “depressive symptoms can be a part of a reaction to medical illness, disability, and/or discomfort” (Zarit & Zarit, 2007). Epidemiological studies suggest that chronic health problems mediate the association between advancing age and depression (Roberts et al, 1997), and depression treatment trials suggest that medical comorbidities, which increase during aging, are risk factors for inferior treatment response (Subramaniam & Mitchell, 2005). Health status thus merits consideration in analyzing changes in mental health with advancing age.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, patients presenting with depression for the first time in later life have an increased risk of physical comorbidities, and physical comorbidity has been associated with a poorer prognosis. 9 While there have been many studies investigating response to pharmacological treatments in middle-aged persons, there have been remarkably few studies specifically focused on assessing interventions in older persons, particularly those with LLD.…”
mentioning
confidence: 99%
“…Moreover, a higher risk of depressive episode onset may be observed among people with a history of depression in comparison to those who do not show any previous episode. Since first episodes tend to appear from adolescence to middle age, late-life depression relapses may adopt more enduring statuses with a poorer prognosis in comparison to other life periods[ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%